Basic study of mobile gamma ray imaging using a digital camera and scintillator. (1st April 2021) - Yoshitani, Hiroshi; Fujibuchi, Toshioh; Nakajima, Yumiko
Abstract: Gamma cameras are used in nuclear medicine examinations involving radioisotopes; however, they do not provide real-time feedback. We propose a real-time imaging method based on a commercially available digital camera and a scintillator array to provide simple and accurate measurements of radioisotope accumulation and contamination. We evaluate the sensitivity and resolution of the proposed device using x-rays as a proxy for gamma-rays. The performance of the device is demonstrated using PENTAX KP and ORCA-spark C11440-36U digital cameras. A caesium iodide scintillator array is irradiated with x-rays, with the state of light emission confirmed using live view images. The pixel value is evaluated as a function of dose rate. Furthermore, we investigate the state of light emission in response to amplifying the light signal using an image intensifier. For the PENTAX KP, luminescence is observable for a dose rate of approximately 10 mSv h −1, which changes to 2.1 mSv h −1 when an image intensifier is used. Notably, the ORCA-spark detected emission at a low dose rate of 0.06 mSv h −1 . However, using an image intensifier resulted in noisier images. Therefore, although the ORCA-spark can observe luminescence at a suitable predicted dose rate for application in nuclear medicine examinations, a collimator is required to control the spread of gamma rays. However, as this causes the sensitivity to decrease, increasing the amount of light emitted by the scintillator and improving the sensitivity of the camera is vital.